Assessing soil erosion potential for prioritization of land risk area in the Sala watershed of Ari zone, South Ethiopia - Debebe, Woldeyes; Yirgu, Teshome; Debele, Mulugeta (Frontiers in Environmental Science, 2025)
Soil erosion has led to land degradation, which affects the environmental and economic sustainability of agricultural land systems. This study aims to assess the annual soil loss potential to prioritize land risk areas in the Sala watershed for conservation planning. Soil sampling and topographic data were the primary sources of data. The secondary sources were satellite imagery and meteorological data. The Revised Universal Soil Loss Equation (RUSLE) model, integrated with GIS and remote sensing (RS) techniques, was used to formulate optimal soil erosion management plans and assess erosion hotspot areas in the study area. The results showed that the distribution of annual soil loss ranged from 1 to 1,875 t/ha/year, and the mean annual soil loss was 312.6 t/ha/year. The findings also revealed that the watershed was classified as having low soil erosion rates (1–162 t ha/year) (31.91%), moderate soil erosion rates (162–405 t ha/year) (39.67%), high soil erosion rates (405–805 t/ha/year) (20.78%), and very high soil erosion rates (800–1875 t/ha/year) (7.64%). 28.42% of the watershed was classified as having high to very high erosion severity, primarily found on steeper slopes and in areas with inappropriate land use practices. In the Sala watershed, soil and water conservation measures have important implications for improving soil fertility and productivity. Thus, effective land management planning should be implemented to achieve sustainable agricultural land use in the study watershed area.